Analisis Debit Banjir Tanggul Bendungan Way Apu Pulau Buru Ambon - Siti Astycha Ananda Sofyan; Andi Adillah Firstania Azis (Departement of Mathematics Education, 2023)
The Way Apu Dam is located on Buru Island, Ambon. It has multiple functions, including Irrigation, Raw Water, Hydropower, and Flood Control. The Way Apu River is a fairly large river which flows through settlements in the Way Apu area in Buru Regency which empties to the southeast into the Seram Sea. In line with the pace of community development, especially those who live and carry out activities around the plains on the downstream of the river, the problems caused by flooding. In July 2021, the embankment of the building that circumvented the Way Apu Dam, which used the 25-year flood plan design, was broken or damaged. Construction on the field has made the cross-sectional design double the design results. So the purpose of this study is to determine the design discharge for a 25 year return period using the HSS, ITB 1, ITB 2 method. From the results of the analysis of the three methods, the one that approaches the planning discharge value is the ITB 1 method with a planning Q25 discharge of 627 m3/s, and the Q25 discharge during the construction period of 768 m3/sec has exceeded the Q25 planning discharge value of 627 m3/sec.